Академическая наука в общественном мнении и в оценках экспертов - Мартынюк, И.; Соболева, Н. (Социология: теория, методы, маркетинг, 2006)
The article is dedicated to the studies of image reflection in public consciousness as well as to the role of modern academic science, its problems, and development prospects. The estimations of eminent scientists and opinions of ordinary people as to the Ukrainian science, its social role in the state organization, investigation level and authority among world scientific community are compared. Based upon acquired empirical data the authors have arrived at the conclusion about perspectives of development of scientific approaches, prestige of scientist profession, and motivation to promote science.